Preparation method of cable shielding layer material

By performing post-treatment steps of drafting, trimming, metal coating, pressing composite and heat treatment on the carbon nanotube film, a composite carbon nanotube film with a "sandwich" structure is formed, which solves the problems of complex preparation process and unstable product quality in the prior art, and realizes the preparation of carbon nanotube film shielding layer material with high strength and excellent electromagnetic shielding performance.

CN119907227APending Publication Date: 2025-04-29BEIJING TANYUAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411889073.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The preparation process of existing carbon nanotube thin film shielding layer materials is complicated, and there are problems such as carbon nanotube aggregation, unstable product quality and unsuitable for large-scale preparation.

Method used

The post-treatment steps are adopted, including drafting treatment, trimming treatment, double-sided metal coating treatment, pressing composite and heat treatment to form a composite carbon nanotube film with a "sandwich" structure.

Benefits of technology

It improves the tensile strength and electromagnetic shielding efficiency of the carbon nanotube film, has stable product quality, is suitable for large-scale production, and has achieved 100% coverage of the cable, reducing the self-weight of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907227A_ABST
    Figure CN119907227A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of shielding layer materials for cables, in particular to a preparation method of a carbon nanotube film shielding layer material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of shielding layer materials for cables, and in particular to a method for preparing a carbon nanotube film shielding layer material. Background Art

[0002] Electromagnetic shielding cable is a cable with electromagnetic shielding performance that has a metal wire braid or metal tape outer shielding layer. The metal shielding layer can prevent interference signals from entering the inner conductor to interfere with the transmission of the signal, while reducing the loss of the transmission signal. In addition, the shielding layer can also prevent electromagnetic interference and electromagnetic radiation by using the reflection, absorption and skin effect of metal on electromagnetic waves. Electromagnetic shielding cables used in aerospace are the "nervous system" of aircraft, playing an important role in transmitting electrical signals for the control system and delivering electrical energy to various airborne equipment. With the upgrading of aerospace aircraft, ultra-lightweight, strong weather resistance and high reliability have become the development requirements of electromagnetic shielding cables. In particular, due to the relatively small space of the aircraft and the complex electromagnetic environment, the cable system must have the ability to effectively resist electromagnetic interference. In addition, the weight reduction of the cable is also of positive significance to increasing the effective load of the aircraft.

[0003] At present, the shielding material of electromagnetic shielding cable is mainly braided copper mesh. This kind of shielding layer has high density and is easy to oxidize, which makes the cable heavy. After the shielding layer is oxidized, its shielding effect is significantly weakened. So far, there is no effective alternative product and solution. In the existing technology, the coverage rate of the braided copper mesh or tinned braided copper mesh shielding layer is about 70-90%, the shielding efficiency is low, and the mass per square meter is about 1.1-1.5 kg, which is heavy.

[0004] Carbon nanotube film is a two-dimensional planar structural material formed by the disordered assembly and arrangement of a large number of carbon nanotubes. It has the advantages of ultra-lightweight, strong weather resistance and high shielding performance. It is the most ideal material to replace the braided copper mesh shielding layer. Using it as a shielding layer can not only achieve the weight reduction effect of the cable, but also greatly improve the reliability of the shielded cable, which has a positive impact on the development of shielded cables for aerospace use.

[0005] However, there are many problems in the preparation of carbon nanotube thin film shielding layer materials in the prior art, such as complicated preparation process, carbon nanotube aggregation, unstable product quality, and unsuitability for large-scale preparation.

[0006] Therefore, it is urgent to develop a new method for preparing carbon nanotube thin film shielding layer materials to solve the current problems such as carbon nanotube aggregation, and the process should be simple, the product quality should be stable, and it should be suitable for large-scale preparation. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a method for preparing a carbon nanotube film shielding layer material.

[0008] The present invention provides a method for preparing a carbon nanotube film shielding layer material, comprising the following steps of post-processing the carbon nanotube film:

[0009] a) stretching the raw material of the carbon nanotube film, wherein the stretching is performed in a dispersant solution with a stretching force of 5-100 N,

[0010] b) optionally performing edge trimming on the stretched carbon nanotube film,

[0011] c) double-sided metal coating treatment of the stretched carbon nanotube film,

[0012] d) Pressing and compounding two or more carbon nanotube films with metal coating to form a composite carbon nanotube film with a "sandwich" structure,

[0013] e) heat treating the composite carbon nanotube film obtained in step d) to achieve diffusion of the interlayer metal coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 These are the shielding effectiveness test results of the composite carbon nanotube films obtained through Examples 1-3 and the comparative example. DETAILED DESCRIPTION

[0015] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments and examples are part of the embodiments and examples of the present invention, rather than all of the embodiments and examples. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The technical solution of the present invention is described in detail below through the following embodiments.

[0016] The present invention provides a method for preparing a carbon nanotube film shielding layer material, comprising the following steps of post-processing the carbon nanotube film:

[0017] a) stretching the raw material of the carbon nanotube film, wherein the stretching is performed in a dispersant solution with a stretching force of 5-100 N,

[0018] b) optionally performing edge trimming on the stretched carbon nanotube film,

[0019] c) double-sided metal coating treatment of the stretched carbon nanotube film,

[0020] d) Pressing and compounding two or more carbon nanotube films with metal coating to form a composite carbon nanotube film with a "sandwich" structure,

[0021] e) heat treating the composite carbon nanotube film obtained in step d).

[0022] Herein, the carbon nanotube film raw material can be prepared by any method known in the art. For example, in some embodiments, the carbon nanotube film raw material can be prepared by chemical vapor deposition (CVD), laser ablation (LA), arc discharge (AD), template method, flame method, solid phase pyrolysis method, glow discharge method, gas combustion method and polymerization reaction synthesis method.

[0023] In some embodiments, the carbon nanotube film raw material is prepared by floating catalytic chemical vapor deposition (FCCVD) by passing a gas containing a carbon source into a reaction chamber at high temperature, and decomposing the gas under the action of a catalyst to generate carbon nanotubes.

[0024] In one embodiment, the thickness of the carbon nanotube film raw material is in the nanometer to micrometer range, for example, 10 nm-1000 μm, for example, 100 nm-500 μm, for example, 1-50 μm, and for example, 3-20 μm.

[0025] In one embodiment, the steps of preparing a carbon nanotube film by floating catalytic chemical vapor deposition (FCCVD) include:

[0026] i) Using methane, acetylene, ethylene, alcohol, etc. as carbon sources, ferrocene as catalyst, and thiophene as auxiliary agent, carbon nanotube aerogel is generated at 1100-1350°C by floating catalysis method;

[0027] ii) The carbon nanotube aerogel generated by the reaction is exported to a roll-to-roll collection device to collect a carbon nanotube film of a certain width and length.

[0028] In one embodiment, the roll-to-roll collection device in step ii) can realize the continuous collection of kilometer-level carbon nanotube film. After the first layer of carbon nanotube film is collected, the second layer of carbon nanotube film is collected and covered on its surface, and the above steps are repeated to obtain a carbon nanotube film roll.

[0029] In one embodiment, the stretching treatment in step a) is achieved by a roll-to-roll stretching device. In one embodiment, the roll-to-roll stretching device can set the tension of the film itself through a tension sensor to achieve stretching densification of the film under different forces and directional arrangement of carbon nanotubes along the stretching force direction. In one embodiment, the dispersant solution used in step a) is a mixture of a solvent, an active agent and a strong acid in a certain proportion. In one embodiment, the volume proportion of the solvent in the dispersant solution used in step a) is 55-80%, the volume proportion of the active agent is 20-35%, and the volume proportion of the strong acid is 5-15%. In one embodiment, the solvent is a mixture of an organic solvent such as ethanol, acetone or n-butanol and water, wherein the volume ratio of water is ≤40%. In one embodiment, the active agent is selected from small molecule dispersants such as sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, or other conjugated molecules or polymer dispersants, such as ethylene vinyl acetate, polyvinyl pyrrolidone, etc. In one embodiment, the strong acid is selected from H2SO4, HNO3, H2O2, HClO4 or KMnO4.

[0030] In one embodiment, step a) further comprises the step of washing the carbon nanotube film after drawing with ethanol or acetone to remove the residual dispersant solution and further densify the carbon nanotube film. In one embodiment, step a) further comprises drying the carbon nanotube film washed with ethanol or acetone at 60-80°C.

[0031] In one embodiment, the trimming process in step b) is performed using a laser cutting device. In the present invention, the trimming process can cut off the uneven area on the edge of the film caused by the drafting process to ensure the uniformity of the film thickness and width.

[0032] In one embodiment, the double-sided metal coating process in step c) is performed on a roll-to-roll coating machine. In one embodiment, the plated metal is selected from one or more combinations of copper, aluminum, nickel, gold, platinum, palladium, silver / copper alloy, copper / nickel alloy, etc. In one embodiment, the plating principle adopted by the coating machine can be chemical plating, or it can be physical vapor deposition (including evaporation technology, sputtering technology, arc technology) or atomic layer deposition method. In one embodiment, the thickness of the metal coating needs to be controlled between 50-800 nm according to the thickness of the narrow band. The thinner the film, the thinner the metal coating applied.

[0033] In one embodiment, the pressing equipment used for the pressing and laminating in step d) is a roll-to-roll press with a heating function. In one embodiment, the thickness of the metal coating on the side to be laminated with other carbon nanotube films is between 50-150 nm. In one embodiment, the thickness of the metal coating on the side not to be laminated with other carbon nanotube films is between 500-800 nm.

[0034] In one embodiment, the heat treatment in step e) can improve the phenomenon that the interlayer bonding force of the composite carbon nanotube film is weak and stratification is easy to occur during use, and realize the diffusion of the interlayer metal coating. In one embodiment, the heat treatment process in step e) is carried out in a vacuum environment. In one embodiment, the temperature of the heat treatment needs to be controlled at 400-800°C, preferably 550-700°C, according to the type of coating. In a specific embodiment, when the coating metal is Ni, the temperature of the heat treatment is 700°C. In a specific embodiment, when the coating metal is Al, the temperature of the heat treatment is 550°C. In a specific embodiment, when the coating metal is Al and Cu, the temperature of the heat treatment is 600°C. In one embodiment, the heat treatment time is 30-120 min, preferably 60-90 min.

[0035] The carbon nanotube film prepared by the existing technology has problems such as low density and disordered arrangement of carbon nanotubes, resulting in poor mechanical strength and electromagnetic shielding performance, which is difficult to meet the requirements of the cable shielding layer. Therefore, it is necessary to improve the strength and electromagnetic shielding performance of the film through post-processing methods.

[0036] The post-processing method of the carbon nanotube film of the present invention can prepare a composite carbon nanotube film material with a tensile strength of more than 200 MPa (good mechanical strength) and an electromagnetic shielding effectiveness of more than 75 dB, and wrap it around the surface of the cable core to form a shielding layer. The product obtained by the preparation method has stable quality and is suitable for large-scale production. The shielding layer of the composite carbon nanotube film material obtained can greatly reduce the dead weight of the cable and has excellent electromagnetic shielding effectiveness. When applied to aircraft, it is of great significance to improve the performance of the aircraft, increase the payload, improve fuel efficiency, and extend the flight distance.

[0037] Example

[0038] The technical solution of the present invention is explained in more detail below through examples and comparative examples, but the content of the present invention is not limited thereto.

[0039] Embodiment 1:

[0040] 1. Prepare and collect three carbon nanotube films with a length of 1100 m, a width of 85-90 mm (uneven width), and a thickness of 5 μm by floating catalytic chemical vapor deposition method;

[0041] 2. The three films were stretched separately. The dispersant solution used in the stretching process was solvent (ethanol: water = 60:40 volume ratio): sodium dodecylbenzene sulfonate: H2SO4 = 70:20:10, and the stretching force was 15 N. After the stretching treatment, the film was cleaned with ethanol to remove the residual dispersant and further shrink and densify the film. The narrow strip of film treated with ethanol was placed in a vacuum environment at 70°C and dried for 60 min.

[0042] 3. Use laser cutting equipment to cut off the uneven parts of the film edge, and finally obtain three kilometer-scale carbon nanotube films A, B, and C with a width of 80 mm and a thickness of 5 μm;

[0043] 4. The carbon nanotube film A is subjected to a roll-to-roll magnetron sputtering ion plating device, and a Ni metal coating is applied on one side (called the A-1 side) with a coating thickness of 500 nm, and a Ni metal coating is also applied on the other side (called the A-2 side) with a coating thickness of 60 nm; the carbon nanotube film B is subjected to a roll-to-roll PVD metal deposition device, and a Ni metal coating is applied on both sides (called the B-1 side and the B-2 side) with a coating thickness of 60 nm; the carbon nanotube film C is subjected to a roll-to-roll PVD metal deposition device, and a Ni metal coating is applied on one side (called the C-1 side) with a coating thickness of 500 nm, and a Ni metal coating is also applied on the other side (called the C-2 side) with a coating thickness of 60 nm;

[0044] 5. Laminate the A-2 surface with the B-1 surface, and the B-2 surface with the C-2 surface. The laminated composite film is pressed and laminated by a roll-to-roll pressing device. The preheating temperature of the pressing roller is set to 100°C, the number of pressing rollers is 5 pairs, and the film passing speed is 2 m / min.

[0045] 6. Place the pressed composite film in a vacuum heat treatment furnace for diffusion annealing at a temperature of 550°C and a vacuum degree of 1×10 -3 Pa, the treatment time is 60 min.

[0046] The composite carbon nanotube film is dense and can achieve 100% coverage of cables. Its mass per square meter is about 2-5g, and its electromagnetic shielding effectiveness can reach more than 80 dB (such as Figure 1 as shown).

[0047] Embodiment 2:

[0048] 1. Prepare and collect three carbon nanotube films with a length of 1060 m, a width of 75-85 mm (uneven width), and thicknesses of 10 μm, 5 μm, and 5 μm respectively by floating catalytic chemical vapor deposition method;

[0049] 2. The three films were stretched separately. The dispersant solution used in the stretching process was solvent (acetone: water = 70:30): sodium dodecylbenzene sulfonate: HNO3 = 60:25:15, and the stretching forces were 20 N, 5 N, and 5 N, respectively. After the stretching treatment, the film was cleaned with ethanol to remove the residual dispersant and further shrink and densify the film. The film treated with ethanol was placed in a vacuum environment at 80°C and dried for 40 min.

[0050] 3. Use laser cutting equipment to cut off the uneven parts of the film edge, and finally obtain three kilometer-scale carbon nanotube films A, B, and C with a width of 70 mm;

[0051] 4. The carbon nanotube film A is subjected to a roll-to-roll ion-assisted evaporation coating device, and an Al metal coating is applied on one side (called the A-1 side) with a coating thickness of 80 nm, and a Ni metal coating is also applied on the other side (called the A-2 side) with a coating thickness of 60 nm; the carbon nanotube film B is subjected to a roll-to-roll PVD metal deposition device, and a Ni metal coating is applied on both sides (called the B-1 side and the B-2 side) with a coating thickness of 60 nm; the carbon nanotube film C is subjected to a roll-to-roll PVD metal deposition device, and a Ni metal coating is applied on one side (called the C-1 side) with a coating thickness of 500 nm, and a Ni metal coating is also applied on the other side (called the C-2 side) with a coating thickness of 60 nm;

[0052] 5. Laminate the A-2 surface with the B-1 surface, and the B-2 surface with the C-2 surface. The laminated composite film is pressed and laminated by a roll-to-roll pressing device. The preheating temperature of the pressing roller is set to 100°C, the number of pressing rollers is 5 pairs, and the film passing speed is 2 m / min.

[0053] 6. Place the pressed composite film in a vacuum heat treatment furnace for diffusion annealing at a temperature of 550°C and a vacuum degree of 1×10 -3 Pa, the treatment time is 60 min.

[0054] The composite carbon nanotube film is dense and can achieve 100% coverage of cables. Its mass per square meter is about 3-6g, and its electromagnetic shielding effectiveness can reach more than 77 dB (such as Figure 1 as shown).

[0055] Embodiment 3:

[0056] 1. Prepare and collect three carbon nanotube films with a length of 1080 m, a width of 75-80 mm (uneven width), and thicknesses of 10 μm, 5 μm, and 5 μm respectively by floating catalytic chemical vapor deposition method;

[0057] 2. The three narrow strips were stretched separately. The dispersant solution used in the stretching process was solvent (n-butanol: water = 65:35): hexadecyltrimethylammonium bromide: HNO3 = 55:35:10, and the stretching forces were 25 N, 10 N and 10 N respectively. After the stretching treatment, the film was cleaned with ethanol to remove the residual dispersant and further shrink and densify the film. The film treated with ethanol was placed in a vacuum environment at 85°C and dried for 30 min.

[0058] 3. Use laser cutting equipment to cut off the uneven parts of the film edge, and finally obtain three kilometer-scale carbon nanotube films A, B, and C with a width of 75 mm each.

[0059] 4. The carbon nanotube film A was subjected to a roll-to-roll atomic layer deposition device, and a Cu metal coating was applied on both sides (called A-1 side and A-2 side) with a coating thickness of 30 nm. Then, an Al metal coating was applied on the Cu metal coating with a coating thickness of 100 nm by a roll-to-roll magnetron sputtering ion coating device. The carbon nanotube film B was subjected to a roll-to-roll atomic layer deposition device, and a Cu metal coating was applied on both sides (called B-1 side and B-2 side) with a coating thickness of 20 nm. Then, an Al metal coating was applied on the Cu metal coating with a roll-to-roll magnetron sputtering ion coating device. The Al coating thicknesses on both sides were 100 nm (B-1 side) and 600 nm (B-2 side). The carbon nanotube film C was subjected to a roll-to-roll atomic layer deposition device, and a Cu metal coating was applied on both sides (called C-1 side and C-2 side) with a coating thickness of 20 nm, and then an Al metal coating is applied on the Cu metal coating by a roll-to-roll magnetron sputtering ion plating device, with the coating thicknesses on both sides being 100 nm (C-1 surface) and 600 nm (C-2 surface), respectively.

[0060] 5. Laminate the A-1 surface with the B-1 surface, and the B-2 surface with the C-1 surface. The laminated composite film is pressed and laminated by a roll-to-roll pressing device. The preheating temperature of the pressing roller is set to 150°C, the number of pressing rollers is 5 pairs, and the passing speed of the film is 1 m / min.

[0061] 6 The laminated film was placed in a vacuum heat treatment furnace for diffusion annealing at a temperature of 500°C and a vacuum degree of 1×10 -3 Pa, the processing time is 80 min.

[0062] The composite carbon nanotube film is dense and can achieve 100% coverage of cables. It has a mass of about 3-5g per square meter and an electromagnetic shielding effectiveness of more than 85 dB (such as Figure 1 as shown).

[0063] Comparative Example:

[0064] A carbon nanotube film with a length of 1100 m, a width of 75-80 mm (uneven width), and a thickness of 20 μm was prepared and collected by floating catalytic chemical vapor deposition. It was densified by spraying ethanol and then dried in a vacuum environment at 85°C for 30 min. The uneven part of the edge of the film was cut off by laser cutting equipment, and finally a kilometer-scale carbon nanotube film with a width of 75 mm was obtained. The carbon nanotube film has a low density and an electromagnetic shielding effectiveness of <50 dB (such as Figure 1 as shown).

Claims

1. A method for preparing a carbon nanotube film shielding layer material, comprising the following steps of post-processing the carbon nanotube film: a) stretching the raw material of the carbon nanotube film, wherein the stretching is performed in a dispersant solution with a stretching force of 5-100 N, b) optionally performing edge trimming on the stretched carbon nanotube film, c) performing double-sided metal coating treatment on the stretched carbon nanotube film to form a metal coating layer, d) pressing and compounding two or more carbon nanotube films with metal coating to form a composite carbon nanotube film with a "sandwich" structure, e) heat treating the composite carbon nanotube film obtained in step d) to achieve diffusion of the interlayer metal coating.

2. The method according to claim 1, wherein the dispersant solution used in step a) is composed of a solvent, an activator and a strong acid.

3. The method according to claim 1 or 2, wherein the volume proportion of the solvent in the dispersant solution is 55-80%, the volume proportion of the activator is 20-35%, and the volume proportion of the strong acid is 5-15%.

4. The method according to any one of claims 1 to 3, wherein the solvent is a mixture of an organic solvent such as ethanol, acetone or n-butanol and water, wherein the volume ratio of water is ≤40%.

5. The method according to any one of claims 1 to 4, wherein the thickness of the metal coating is between 50-800 nm. 6 . The method according to claim 1 , wherein the thickness of the metal coating on the side to be composited with other carbon nanotube films in step c) is between 50-150 nm.

7. The method according to any one of claims 1 to 6, wherein the thickness of the metal coating on the side not composited with other carbon nanotube films in step c) is between 500-800 nm.

8. The method according to any one of claims 1 to 7, wherein the metal plated in step c) is selected from one or more combinations of copper, aluminum, nickel, gold, platinum, palladium, silver / copper alloy, copper / nickel alloy, etc.

9. The method according to any one of claims 1 to 8, wherein the temperature of the heat treatment in step e) is 400-800°C, preferably 550-700°C.

10. The method according to any one of claims 1 to 9, wherein the heat treatment time in step e) is 30-120 min, preferably 60-90 min.